Модернизация как фактор сохранения социального гомеостаза - Погосян, В. (Iнститут соціології НАН України, 2009)
Proceeding from the concept of local civilizations, idea of variability and the theory of functioning of complex systems the author considers modernization as a factor of stability of social system. Macro-sociological discourse and a retrospective view allow presenting modernization as a normative category of historical sociology, on a level with evolution, revolution and convergence. Different societies have rather homogeneous technological equality, but socio- cultural component of a concrete society is constant and unique. It also causes specificity and dynamics of transformations of society, being the kind of genetic protection. The stability of socio-cultural components became reflection of the general historical tradition in the decision of problems of interactions between civilizations. A socio- cultural constant of a concrete society, as a system generating component, aspires to keep a homeostasis, being the condition of relative stability of a society. Social modernization in this case acts as a reflection of social system on exogenous influence. Keeping stable the own matrix base, the system makes partial modernization, correcting certain parameters notable for backlog, in order to enhance own stability and viability.